Pemphigus vulgaris‐associated Kaposi's sarcoma: response to paclitaxel and review of the literature. (17th December 2013) - Balighi, K.; Daneshpazhooh, M.; Aghazadeh, N.; Hejazi, P.; Aryanian, Z.; Azizpour, A.; Rahbar, Z.; Goodarzi, A.; Chams‐Davatchi, C.
Abstract Systemic corticosteroids have long been the mainstay of treatment for pemphigus patients. However, the necessity of their high‐dose and long‐term administration has brought about a number of complications, sometimes causing significant morbidities. Maintaining a balance between therapeutic and undesirable effects of medications is not always easily achievable. Therefore, additional treatment modalities are frequently needed to control side‐effects. Kaposi's sarcoma (KS) is a rare, potentially life‐threatening complication in this setting. Due to the rarity of data on pemphigus‐associated KS treatment, the best therapeutic approach is still undecided. Here, we report two cases of pemphigus patients who had developed extensive KS as a result of severe immunosuppressive therapy and were successfully treated with paclitaxel. In addition, we performed a review of literature to assess the results of the previously employed treatment modalities in this setting.